Stress-Induced Microglia Activation and Monocyte Trafficking to the Brain Underlie the Development of Anxiety and Depression - Ramírez Chan, Karol Gabriela (2016)
Psychosocial stress is capable of causing immune dysregulation and increased neuroinflammatory signaling by repeated activation of the neuroendocrine and autonomic systems that may contribute to the development of anxiety and depression. The stress model of repeated social defeat (RSD) recapitulates many of the stress-driven alterations in the neuroimmune system seen in humans experiencing repeated forms of stress and associated affective disorders. For example, RSD-induced neuronal and microglia activation corresponds with sympathetic outflow to the peripheral immune system and increased ability of bone marrow derived myeloid progenitor cells (MPC) to redistribute throughout the body, including to the central nervous system (CNS), reinforcing stress-associated behaviors. An overview of the neuroendocrine, immunological, and behavioral stress-induced responses will be reviewed in this chapter using RSD to illustrate the mechanisms leading to stress-related alterations in inflammation in both the periphery and CNS, and stress-related changes in behavioral responses.